Assessment of Radiation Absorbed Dose and Cancer Risk in Head Computed Tomography Examinations (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background:The advanced development of computed tomography, which has become widely used, has increased interest and concerns about the risks of radiation dose to the patient. This research intended to calculate the effective doses received by adult patients undergoing head CT examinations and estimate the risk of developing cancer.Materials and Methods:A total of 278 patients of mixed gender, 134 males and 144 females, received head CT. Clinical parameters were obtained from archived CT image files. For this study, the volume computed tomography dose index (CTDIvol), dose length product (DLP), and effective dose (E) were used to express the CT dose. In addition, WAZA-ARI v2 was used to estimate the organ dose values, effective dose, and radiation risks.Results:Mean ±SD values CTDIvol were as follows: for head examination for males and females with contrast were 300.2±81.54 mGy and 165.33±46.38 mGy respectively, and non-contrast were 102.24± 33.18 mGy and 97.63 ± 26.78mGy respectively. For males and females, the mean±SD values DLP for the head with contrast were 4899.6 ± 1229.62 mGy.cm, and 2235.73± 604.93 mGy.cm, respectively, and non-contrast were   1307.16 ±431.39 and 1203.07± 336.43mGy.cm respectively.The mean effective doses which had been received by the patients from a CT examination for the head, for males and females with contrast were 5.71 ± 2.02 mSv and 4.47 ± 1.21mSv respectively, and non-contrast were 2.35 ± 0.78 mSv and 2.41± 0.67 mSv, respectively.The cancer risks probability per ED103 and ED60 for males were 6.4X10^5 and 3.1X10^5 respectively, while for females were7.3X10^5 and 3.9X10^5 respectively.Conclusion:CT scan of the head found, for males and females, that the radiation dose values for DLP, E, and CTDI increased with contrast examinations. The radiation dose values obtained in this research were slightly higher than the values observed in the literature.